2020
DOI: 10.5897/jat2020.0399
|View full text |Cite
|
Sign up to set email alerts
|

Role and contribution of administrative accounting to small and very small businesses

Abstract: The aim of this work is to study the main factors that influence the collaboration between the firm and a cost specialist. The paper highlights key aspects of administrative accountings activities performed by Small and medium enterprises (SMEs) and factors that differentiate them due to their nature and small size. Empirical research was conducted through questionnaires to Greek small and micro (very small) firms. Data were processed through a multiple regression analysis, while the results emphasize the impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Apabila keterampilan akuntansi pada pegawainya meningkat maka akan semakin baik kinerja yang mendukung pada keberlanjutan usaha. Hasil ini sejalan dengan penelitian (Karagiorgos et al, 2020) tentang pentingnya keterampilan akuntansi keuangan sebagai keterampilan akuntansi dasar yang memungkinkan seseorang bekerja secara efisien dan efektif dengan percaya diri dan efektif dalam menjalankan fungsi pencatatan transaksi bisnisnya sehari-hari. Sehingga untuk kegiatan bisnis tidak dapat dilakukan secara efisien tanpa bantuan keterampilan akuntansi.…”
Section: Pengaruh Accounting Skills Terhadap Keberlanjutan Umkmunclassified
“…Apabila keterampilan akuntansi pada pegawainya meningkat maka akan semakin baik kinerja yang mendukung pada keberlanjutan usaha. Hasil ini sejalan dengan penelitian (Karagiorgos et al, 2020) tentang pentingnya keterampilan akuntansi keuangan sebagai keterampilan akuntansi dasar yang memungkinkan seseorang bekerja secara efisien dan efektif dengan percaya diri dan efektif dalam menjalankan fungsi pencatatan transaksi bisnisnya sehari-hari. Sehingga untuk kegiatan bisnis tidak dapat dilakukan secara efisien tanpa bantuan keterampilan akuntansi.…”
Section: Pengaruh Accounting Skills Terhadap Keberlanjutan Umkmunclassified
“…The results agree with Saraiva, Bezerra, and Beiruth (2020), who argued that the cultivation of accounting skills by SMEs' managers and operators, enhances their business understanding, thereby allowing them to have a thorough knowledge of the business. While Karagiorgos, Alexandra, Ignatiou, and Terzidou (2020) argue that the possession of these abilities would strengthen their companies as well as eradicate early failure, Gidado and Babakura (2019) argue that gaining these skills would encourage them to work efficiently, professionally, cost-effectively, and successfully in the process of carrying out everyday business transactions.…”
Section: Figure 3: Age Groupmentioning
confidence: 99%
“…This issue was reiterated by Estrin, Mickiewicz, Stephan, and Wright (2019), who asserted that in transition economies such as South Africa, entrepreneurship and SME development remain lower than in other developing countries. Scholars such as Bongomin, Ntayi, Munene, and Malinga (2017), Salaudeen (2018), Maziriri, Madinga and Mapuranga (2018), and Karagiorgos, Alexandra, Ignatiou, and Terzidou (2020) observed that the rate of failure is attributable to the fact that South African SMEs are unable to resolve the major obstacles of access to finance, budgeting and accounting skills and that ultimately gives birth to poor financial awareness, resulting in the inability to obtain the required resources that will contribute to SME sustainability. Unfortunately, South Africa's unemployment rate is the highest in the world due to SMEs being unsustainable (Ranchhod, 2019;Naidoo, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nketsiah (2018) opines that the role of SMEs in economic development cannot be overstated. As such, SMEs could be considered as the backbone of a country's economy (Karagiorgos et al 2020) and play a crucial role in nation building. Mohamed, Yasseen and Nkhi (2020) noted that the role of SMEs within the South African context remains at the forefront of policy discussions, especially because SMEs contribute to accelerated socio-economic expansion, such as poverty alleviation.…”
Section: Introductionmentioning
confidence: 99%